Awareness about Management of Pain and Anxiety during Dental Treatments among Dental Students - Gayathri. P. S; Krithika.C; Arun Kumar T.M; Selvarathi K; Christy Jospeh Samuel. K; Manju.J (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Humans are more likely to feel contented with a familiar experience however discomfortwith a novel one. The issues of pain, anxiety and fear are always a major part of dentistry. Dental anxietywill result in avoidance of dental care. The initial interaction between the dentist and the patient can revealthe presence of dental anxiety. Aim: This study was aimed assess the awareness about the management ofpain and anxiety during dental treatment among dental students. Methodology: A cross sectional studywas conducted using self-administrated questionnaire, through Google forms using various social mediaplatforms such as whatsapp, facebook among 200 dental students from third year to final year in TamilNadu, India during COVID-19 pandemic lockdown period. Statistics was done and tabulated. Results:It was observed that 80% participants feel interrelation between dental anxiety and pain and 89% believeoffice environment and dental staff affects patient mind-set. 65.5% considers pharmacological route of painmanagement as effective strategy with 48.5% preferring conscious sedation and 36.5% accepts sedation caneliminate the use of local anesthesia. Conclusion: From the present study we would like to conclude thatmost of the dental students were aware about pain and anxiety management during dental treatments howeverfurther educational improvement regarding pain and anxiety in emergency conditions, especially concerningthe assessment methods and continuity in the control of pain might result in better patient satisfaction.